Efficiency through the built environment a case study of Land Transportation Regional Offices in Mindanao - Canuto, Agnes S. (2014)
The design and control of heavily crowded facilities occupied by unfamiliar users for special transactions shall be considered to uphold the development of efficient and safe operations within these public spaces. Crowding incidences in such spaces, as well as slow transaction processes and personal concerns due to the physical and thermal setting of the building is apparent. The main reason of such condition is the poor and systematic planning and design (Promoting Space Efficiency in Building Design, 2004). With this, the researcher came to a question: what architectural components should be incorporated in the design of the Land Transportation Office (LTO) to achieve efficiency as measured by time? The researcher proposes that spatial efficiency leads to efficient operations and so, this study had its primary concept of identifying the relationship of these two factors. Generally, this study aimed to create an efficient Land Transportation Office that would generate a systematic and organized transaction flow consequently minimizing durations of transactions and overcrowding. Using a case study method, the conditions of the existing Regional Land Transportation Offices I Mindanao were observed and analyzed for the assessment and formulation of the design guidelines for an efficient Land Transportation Office (LTO). Gathered data showed that the factors which affect the efficiency in the said office include: (1) The pattern of the flow of transaction and queuing, (2) Common practices within the office, (3) Satisfaction of users and end-users, and (4) The built environment. The assessment of these physical and non-physical factors was the basis of the development of the design guidelines presented in this study.